2016
DOI: 10.1016/j.chest.2016.02.359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients With Chronic Obstructive Pulmonary Disease With Comorbid Bronchiectasis: A Systemic Review and Meta-analysis

Abstract: Background: In the 2014 Global initiative for chronic Obstructive Lung Disease guidelines, bronchiectasis was for the first time defined as a comorbidity of chronic obstructive pulmonary disease (COPD), and this change has been retained in the 2015 update, which emphasizes the influence of bronchiectasis in the natural history of COPD. The present meta-analysis was aimed at summarizing the impact of bronchiectasis on patients with COPD. Methods: Databases including Embase, PubMed, and the Cochrane Central Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 36 publications
(72 reference statements)
0
39
0
4
Order By: Relevance
“…Other features that distinguished patients with COPD and bronchiectasis from COPD alone included greater daily sputum production, higher exacerbation frequency, worse lung function, higher levels of inflammatory biomarkers, increased colonisation by potential pathogenic micro-organism (PPM) and increased rate of Pseudomonas aeruginosa ( P. aeruginosa ) colonisation. 16 A systematic review and meta-analysis of 14 observational studies in COPD patients found that the presence of bronchiectasis was associated with worse airflow obstruction, isolation of PPM, increased risk of exacerbation and of mortality. 17 …”
Section: Sectionmentioning
confidence: 99%
“…Other features that distinguished patients with COPD and bronchiectasis from COPD alone included greater daily sputum production, higher exacerbation frequency, worse lung function, higher levels of inflammatory biomarkers, increased colonisation by potential pathogenic micro-organism (PPM) and increased rate of Pseudomonas aeruginosa ( P. aeruginosa ) colonisation. 16 A systematic review and meta-analysis of 14 observational studies in COPD patients found that the presence of bronchiectasis was associated with worse airflow obstruction, isolation of PPM, increased risk of exacerbation and of mortality. 17 …”
Section: Sectionmentioning
confidence: 99%
“…Mortality was only slightly higher in the subgroup with many comorbidities and evidence of systemic inflammation. Bronchiectasis A meta-analysis of six observational studies demonstrated a correlation between the detection of bronchiectasis in (high-resolution) computed tomography in patients with COPD and the frequency of exacerbations (weighted mean difference 1.54 times in the previous year) [14]. Since these patients with bronchiectasis had more chronic colonisation by pathogenic microorganisms (odds ratio 7.33) and a higher rate of Pseudomonas aeruginosa isolation (odds ratio 3.5), this coexistence is considered a potential mechanism for frequent exacerbations.…”
Section: Severe Airflow Limitationmentioning
confidence: 99%
“…There has only been one study analysing the impact of bronchiectasis on the quality of life Finally, one of the most consistently evident factors is the propensity of patients with bronchiectasis-associated COPD to have not only more exacerbations [14][15][16][17] but also ones that are more severe 13,15,17,20 and longer-lasting 9 , although not all authors have found this association 18,19,24 . Taken together, however, both the meta-analyses 28,29 found a relationship between exacerbations and bronchiectasis ( Table 3).…”
Section: Prognostic Impact Of Bronchiectasismentioning
confidence: 85%
“…These differences are not limited to clinical factors but also involve functional, microbiological, inflammatory and even prognostic and therapeutic factors, which has led some authors to conclude that there is a specific clinical phenotype of COPD patients with bronchiectasis. Table 3 shows the results of the two meta-analyses published to date 28,29 .…”
Section: Bronchiectasis In Patients With Copd Prevalencementioning
confidence: 99%